DESIGN AND DEVELOPMENT OF A SINGLE PAGE AND WEB-BASED RESPONSIVE E-LEARNING SYSTEM FOR HIGHER EDUCATION INSTITUTIONS - Muhammad Lookman Hossain Khan, - (2019)
Students now use not only computers or laptops, but also small devices such as mobile phones. The students at Higher Education Institutions spent a lot of time on the Internet to find the course materials. Sometimes the teacher sends the materials, but the students who are willing to take a specific course of a semester cannot get a brief concept of the course on before starting the semester. There is now a lot of online education systems on the Internet, but few are a single page and responsive. The purpose of this research is to develop a single page, responsive and web-based e-learning system. The method used in this research is the Rapid Application Development approach which has six stages of the development process, namely Planning, Analysis, Design, Implementation, Testing, and Maintenance. This research was conducted in the Faculty of Technology and Vocational Education, Universitas Pendidikan Indonesia. The students and teachers from the Department of Mechanical Engineering Education participated in this research. The results of this research indicate that with fully functional live chat, the OpenCourseWare system has a high usability test score, highly responsive and awesome features. The OpenCourseWare system is responsive and ajax-based mobile-friendly system that can be used by higher education institutions as an e-learning system based on the results obtained.---- Mahasiswa sekarang tidak hanya menggunakan komputer atau laptop, tetapi juga perangkat kecil seperti ponsel. Para mahasiswa di Lembaga Pendidikan Tinggi menghabiskan banyak waktu di Internet untuk menemukan materi pelajaran. Kadang-kadang guru mengirim materi, tetapi siswa yang mau mengambil kursus khusus semester tidak bisa mendapatkan konsep singkat kursus sebelum memulai semester. Akhir-akhir ini ada banyak sistem pendidikan online di Internet, tetapi hanya sedikit yang Single Page dan responsif. Tujuan dari penelitian ini adalah untuk mengembangkan sistem e-learning Single Page, responsif dan berbasis web. Metode yang digunakan dalam penelitian ini adalah Rapid Application Development approach yang memiliki enam tahap proses pengembangan, yaitu Planning, Analisis, Design, Implementation, Testing, dan Maintenance. Penelitian ini dilakukan di Fakultas Pendidikan Teknologi dan Pendidikan Kejuruan, Universitas Pendidikan Indonesia. Para mahasiswa dan guru dari Departemen Pendidikan Teknik Mesin berpartisipasi dalam penelitian ini. Hasil penelitian ini menunjukkan bahwa dengan live chat yang berfungsi penuh, sistem OpenCourseWare memiliki skor tes kegunaan yang tinggi, fitur yang sangat responsif dan mengagumkan. Sistem OpenCourseWare adalah sistem mobile-friendly yang responsif dan berbasis ajax yang dapat digunakan oleh lembaga pendidikan tinggi sebagai sistem e-learning berdasarkan hasil yang diperoleh.